Neuropharmacological Effects of Mesaconitine: Evidence from Molecular and Cellular Basis of Neural Circuit. (21st August 2020) - Sun, Zhihui; Yang, Limin; Zhao, Lihong; Cui, Ranji; Yang, Wei
Abstract : Mesaconitine (MA), a diester-diterpenoid alkaloid in aconite roots, is considered to be one of the most important bioactive ingredients. In this review, we summarized its neuropharmacological effects, including analgesic effects and antiepileptiform effects. Mesaconitine can act on the central noradrenergic system and the serotonin system; behaving like the norepinephrine reuptake inhibitors and tricyclic antidepressants that increase norepinephrine levels in stress-induced depression. Therefore, the possible perspectives for future studies on the depression of MA were also discussed as well. The pharmacological effect of MA on depression is worthy of further study.